Updated checklist of Poa in the Iberian Peninsula and Balearic Islands - Ana Ortega-Olivencia; Juan A. Devesa (PhytoKeys, 2018)
Based on our study of 4,845 herbarium sheets of the genus Poa from the area covered by Flora iberica, namely, the Iberian Peninsula and the Balearic Islands, we recognise 24 taxa (17 species, 1 subspecies and 8 varieties), mostly perennials. Most of these taxa have wide global and/or European distributions, while two (P. legionensis and P. minor subsp. nevadensis) are Spanish endemics and two have restricted distributions (P. ligulata, Iberia–North Africa; P. flaccidula, Iberia–North Africa and the Balearic Islands, extending to Provence, France). We have studied the original publications of more than 225 names considered as synonyms, with those more historically cited in Flora iberica taken into account in this paper; a total of 26 are new synonyms. The following names are typified: P. alpina var. involucrata Lange, P. annua var. lanuginosa Sennen, P. minor subsp. nevadensis Nannf., P. paui Font Quer, P. sulcata Lag. and P. trivialis var. flaccida Willk. ex J.J. Rodr. We include P. compressa L. in the flora of Portugal for the first time and present detailed illustrations of three very interesting taxa (P. legionensis, P. minor subsp. nevadensis and P. ligulata). In addition to a general species key, we provide the following information for each taxon: synonyms, types, typification, the most relevant iconography, regional flowering time, regional and general distribution and, as supplementary material, the number of sheets examined and a list of selected materials.